PERGESERAN FUNGSI TARI KONCONG PADA SUKU DAYAK KANAYATN DI DESA BABANE KECAMATAN SAMALANTAN KABUPATEN BENGKAYANG - Imelda, Brigita; Ismunandar, Ismunandar; Istiandini, Winda (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe research is carried upon the researcher’s great curiosity toward the function of Koncong Dance among Kanayatn Dayaknese in Babane Village Bengkayang District.It used to be functioned as a ritual dance which is now shifted into a mere performance.The problems in this research are Koncong dance’s ritual function and performance function, and the function shifting on Koncong dance among Kanayatn dayaknese in Babane Village Samalantan Sub-District Bengkayang District. The research implementation plan in cultural arts and dance skills learning in Junior High Level.The method used was descriptive in form of qualitative with anthropology approach.The data was obtained through observation, interview, and documentation. The data validation technique are triangulation and observation extension technique, and the data analysis was anthropology observation with analysis technique when the research was on process.Based on the data analysis, it can be concluded that Koncong dance among Kanayatn dayaknese in Babane village Samalantan sub-district Bengkayang District is a ritual dance that functioned as a treatment media for ill people which function is then shifted into a performance art in order to preserve it. The Koncong dance’s function a treatment for ill people ritual is shifted into a performance art because today’s young generations are unable to preserve it and it is also eroded by the modern age. This research result can be an option for a teaching material in culture arts learning in Junior High School.Key Words: Function shifting, Koncong dance, Kanayatn dayaknese, Bengkayang